2015
DOI: 10.1097/ijg.0b013e318207069b
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 Expression and Retinal Cell Death in a Transgenic Mouse Model for Acute Angle-Closure Glaucoma

Abstract: PURPOSE: PAX6 is a highly conserved protein essential for the control of eye development both in invertebrates and vertebrates. PAX6 expression persists in the adult inner retina, but little is known about its functions after completion of retinal differentiation. Therefore, we investigated PAX6 expression in wild-type and calcitonin receptor-like receptor transgenic (CLR) mice with angle-closure glaucoma. METHODS: Intraocular pressure was measured by indentation tonometry in anesthetized mice. Eyes of mice of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…PAX6 expression in the retina is detectable up to 79 years of age in donors and is predominantly localized in the GCL and the inner part of the INL [ 119 ]. In mouse retinas, PAX6 protein levels are high at P5, decrease to intermediate levels at P21, and remain constant thereafter at least until P428 [ 120 ]. In two models of retinal degeneration (rd10 mice and light-induced retinal degeneration), it has been revealed that photoreceptor injury causes PAX6-positive Müller cell nuclei to relocate from their normal position in the middle of the INL toward the outer INL and even into the inner part of the ONL.…”
Section: The Role Of Transcription Factors During Retinal Aging and Age-related Degenerationmentioning
confidence: 99%
“…PAX6 expression in the retina is detectable up to 79 years of age in donors and is predominantly localized in the GCL and the inner part of the INL [ 119 ]. In mouse retinas, PAX6 protein levels are high at P5, decrease to intermediate levels at P21, and remain constant thereafter at least until P428 [ 120 ]. In two models of retinal degeneration (rd10 mice and light-induced retinal degeneration), it has been revealed that photoreceptor injury causes PAX6-positive Müller cell nuclei to relocate from their normal position in the middle of the INL toward the outer INL and even into the inner part of the ONL.…”
Section: The Role Of Transcription Factors During Retinal Aging and Age-related Degenerationmentioning
confidence: 99%
“…In mouse retinas, PAX6 protein levels are high at P5, decrease to intermediate levels at P21, and remain constant thereafter at least until P428 [122]. In two models of retinal degeneration (rd10 mice and light-induced retinal degeneration), it has been revealed that photoreceptor injury causes PAX6-positive Müller cell nuclei to relocate from their normal position in the middle of the INL toward the outer INL and even into an inner part of the ONL.…”
Section: The Role Of Transcription Factors During Retinal Aging and Age-related Degenerationmentioning
confidence: 99%